An HIV Narrative of Female Inmates With a Lifetime History of Mental Illness in Durban, South Africa - Naidoo, Samantha; Ferreira, Liezel; Subramaney, Ugasvaree; Paruk, Saeeda (Frontiers in Psychiatry, 2021)
South Africa (SA) has one of the highest prevalence rates of Human Immuno-deficiency Virus (HIV) globally, with women carrying a larger burden of the disease. Furthermore, female inmates have higher rates of HIV compared to their male counterparts, with an over-representation of mental illnesses among female inmates as well. Additionally, mental illnesses are highly prevalent in people living with HIV, with HIV and mental illness sharing a complex bidirectional relationship. This study, which forms part of a larger two-phased, mixed-methods study, describes the experiences of contracting and living with/being affected by HIV, among female inmates with a lifetime history of mental illness, in a South African setting. Method This study was conducted at a correctional centre in Durban, KwaZulu-Natal, SA. Fourteen adult (18 years and older) female inmates, were purposively selected to participate in individual, in-depth semi-structured interviews. Participants had a lifetime history of mental illness, trauma and were either living with HIV, or affected by HIV. Women from diverse cultural backgrounds, who were fluent in English, were selected. This manuscript focuses on the description of the HIV component of the qualitative interviews only. Thematic analysis was used to analyse the data. Results Themes related to contracting HIV included intimate partner betrayal, gender differences regarding sexual behaviour, fear associated with HIV and the importance of pre- and post-test HIV counselling. Themes related to living with/being affected by HIV included the challenges women experienced in their home community, which contrasted with their experience of living with HIV in the prison community, and the importance of accepting an HIV positive life. Conclusion HIV is prevalent in the female inmate population at this correctional centre in SA. This study emphasises that whilst incarcerated, attempts should be made to educate, train, support and manage HIV in this population, thereby helping to curb the epidemic. Further research should aim at exploring such strategies. The study also underscores the importance of the continued need for HIV education in order to eradicate associated stigma and discrimination which are still prevalent in SA.